2000
DOI: 10.1023/a:1002443012525
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: During growth of Methanobacterium thermoautotrophicum in a fed-batch fermentor, the cells are confronted with a steady decrease in the concentration of the hydrogen energy supply. In order to investigate how the organism responds to these changes, cells collected during different growth phases were examined for their methanogenic properties. Cellular levels of the various methanogenic isoenzymes and functionally equivalent enzymes were also determined. Cells were found to maintain the rates of methanogenesis b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Furthermore, some methanogens are known to metabolize carbon monoxide (Oelgeschläger and Rother, 2009 ; Ferry, 2010 ). A physiological characteristic of methanogens is that they may vary their growth to product yield (Y ( x / CH 4) ) upon experiencing a change in environmental conditions—a mechanism commonly referred to as uncoupling (Mountfort and Asher, 1979 ; Archer, 1985 ; Fardeau and Belaich, 1986 ; Tsao et al, 1994 ; Liu et al, 1999 ; Pennings et al, 2000 ; Ver Eecke et al, 2013 ; Bernacchi et al, 2014 ; Taubner et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some methanogens are known to metabolize carbon monoxide (Oelgeschläger and Rother, 2009 ; Ferry, 2010 ). A physiological characteristic of methanogens is that they may vary their growth to product yield (Y ( x / CH 4) ) upon experiencing a change in environmental conditions—a mechanism commonly referred to as uncoupling (Mountfort and Asher, 1979 ; Archer, 1985 ; Fardeau and Belaich, 1986 ; Tsao et al, 1994 ; Liu et al, 1999 ; Pennings et al, 2000 ; Ver Eecke et al, 2013 ; Bernacchi et al, 2014 ; Taubner et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…P me can be related to ∆G reac via P me = ∆G reac M , where M is the production rate of the metabolic byproduct in units of mol g −1 s −1 . In studies we reviewed M ≤ 10 −4 mol g −1 s −1 (Müller et al 1986;Patel et al 1978;Patel & Roth 1977;Pennings et al 2000;Perski et al 1981;Schönheit & Beimborn 1985;Takai et al 2008;Zinder & Koch 1984) and we adopt this as our upper limit, providing our second constraint:…”
Section: D1 Thermodynamics Of Metabolic Gas Productionmentioning
confidence: 99%
“…Methanogens are well known for a variety of astonishing morphological and ecophysiological features. One of these ecophysiological features is their ability to grow hydrogenotrophically while varying their growth-to-product-yield Y —a mechanism also referred to as uncoupling [ 6 , 10 , 40 , 44 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. Uncoupling in methanogens occurs when environmental factors ( i.e.…”
Section: Ecophysiological Characteristics Of Methanogensmentioning
confidence: 99%
“…As a consequence of changing environmental factors methanogens react rapidly by altering their metabolism redirecting the carbon flux to either biomass formation or to maintaining cellular homoeostasis. As an example it has been found that Methanobacterium thermoautotrophicum responds to variations in H concentration by differentially expressing methenyl-tetrahydromethanopterin dehydrogenase and methyl coenzyme M reductase isoenzymes [ 77 ]. Other examples include the varying Y in Methanothermobacter marburgensis upon exposure to different ammonia concentration or dilution rates [ 40 , 44 ].…”
Section: Ecophysiological Characteristics Of Methanogensmentioning
confidence: 99%